2008
DOI: 10.1196/annals.1433.003
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Renal α‐Dicarbonyl Compounds Generated following Ureteral Obstruction by Kidney‐Specific α‐Dicarbonyl/l‐Xylulose Reductase

Abstract: Renal unilateral ureteral obstruction (UUO) causes acute generation of alpha-dicarbonyl stress substances, such as glyoxal, 3-deoxyglucosone, and methylglyoxal, in the kidneys. These alpha-dicarbonyl compounds are prone to form advanced glycation end products (AGEs) via the nonenzymatic Maillard reaction. Using transgenic (Tg) mice overexpressing a kidney-specific short-chain oxidoreductase, alpha-dicarbonyl/L-xylulose reductase (DCXR), we measured generation of alpha-dicarbonyls following UUO by means of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…It is hypothesized that reduction of dicarbonyl compounds by DCXR could provide a detoxification function and result in reduced advanced glycation end-product accumulation (13). Consistent with this hypothesis, it was found that renal α-dicarbonyl compounds were decreased in DCXR-transgenic mice after renal unilateral ureteral obstruction (35), and that diabetic symptoms were reduced when DCXR-transgenic mice were crossed to the KK-A y diabetic model (36). These results suggest that the level of xylulose reductase activity may be important under some disease conditions.…”
Section: Discussionmentioning
confidence: 69%
“…It is hypothesized that reduction of dicarbonyl compounds by DCXR could provide a detoxification function and result in reduced advanced glycation end-product accumulation (13). Consistent with this hypothesis, it was found that renal α-dicarbonyl compounds were decreased in DCXR-transgenic mice after renal unilateral ureteral obstruction (35), and that diabetic symptoms were reduced when DCXR-transgenic mice were crossed to the KK-A y diabetic model (36). These results suggest that the level of xylulose reductase activity may be important under some disease conditions.…”
Section: Discussionmentioning
confidence: 69%
“…To the contrary, it was reported that in patients with diabetes, the accumulation of AGEs significantly inhibited collagen I biosynthesis on human skin fibroblasts 25,43 . Recently, it was demonstrated that AGEs downregulated the expression of protein and message of type III collagen in rat cardiac fibroblasts and mice kidney cells through multiple signaling pathways, such as MAPK and RAGE 41,44 . These results indicated that the influence of AGEs on collagen synthesis varied with cell type, and the related regulation mechanism remained to be elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…In a search for carbonyl‐metabolizing enzymes that might contribute to the reduction of renal carbonyl stress, the role of Dcxr was investigated using rodent models including mice and rats (Sudo et al , ; Asami et al , ; Odani et al , ). High expression of mouse Dcxr in the brush border epithelium of renal tubules was described previously (Nakagawa et al , ) and implied a potential role in the detoxification of AGE‐precursors in the kidney.…”
Section: Catalytic Activity Of Human Dcxrmentioning
confidence: 99%